The Efficacy and Safety of Ischemic Stroke Therapies: An Umbrella Review - Li, Yongbiao; Cui, Ruyi; Fan, Fangcheng; Lu, Yangyang; Ai, Yangwen; Liu, Hua; Liu, Shaobao; Du, Yang; Qin, Zhiping; Sun, Wenjing; Yu, Qianqian; Liu, Qingshan; et al. (Frontiers in Pharmacology, 2022)
Background: Ischemic stroke is a leading cause of morbidity and mortality in neurological diseases. Numerous studies have evaluated the efficacy and safety of ischemic stroke therapies, but clinical data were largely inconsistent. Therefore, it is necessary to summarize and analyze the published clinical research data in the field. Objective: We aimed to perform an umbrella review to evaluate the efficacy and safety of ischemic stroke therapies. Methods: We conducted a search for meta-analyses and systematic reviews on PubMed, the Cochrane Library, and the Web of Science to address this issue. We examined neurological function deficit and cognitive function scores, quality of life, and activities of daily living as efficacy endpoints and the incidence of adverse events as safety profiles. Results: Forty-three eligible studies including 377 studies were included in the umbrella review. The results showed that thrombolytic therapy (tPA; alteplase, tenecteplase, and desmoteplase), mechanical thrombectomy (MTE), edaravone with tPA, stem cell-based therapies, stent retrievers, acupuncture with Western medicines, autologous bone marrow stromal cells, antiplatelet agents (aspirin, clopidogrel, and tirofiban), statins, and Western medicines with blood-activating and stasis-dispelling herbs (NaoShuanTong capsule, Ginkgo biloba, Tongqiao Huoxue Decoction, Xuesaitong injection) can improve the neurological deficits and activities of daily living, and the adverse effects were mild for the treatment of ischemic stroke. Moreover, ligustrazine, safflower yellow, statins, albumin, colchicine, MLC601, salvianolic acids, and DL-3-n-butylphthalide showed serious adverse events, intracranial hemorrhage, or mortality in ischemic stroke patients. Conclusion: Our study demonstrated that tPA, edaravone and tPA, tPA and MTE, acupuncture and Western medicines, and blood-activating and stasis-dispelling herbs with Western medicines are the optimum neurological function and activities of daily living medication for patients with ischemic stroke. Systematic Review Registration: https://inplasy.com/, identifier [INPLASY202250145].